ANALYSIS OF THE ECOPEDAGOGICAL APPROACH IN GEOGRAPHY LEARNING ON THE LEVEL OF ECOLOGICAL INTELLIGENCE OF ADIWIYATA HIGH SCHOOL STUDENTS IN PEKANBARU - Titis Indriani Santoso; Ernawati Ernawati (GeoEco, 2026)
Geography learning grounded in an ecopedagogical approach plays an important role in fostering students’ ecological intelligence, particularly in the context of contemporary environmental challenges. This study aims to examine the implementation of ecopedagogical approaches in geography learning, analyse students’ levels of ecological intelligence, and investigate the influence of ecopedagogical approaches on students’ ecological intelligence. This research employed a survey method with a mixed-methods sequential explanatory design involving 7 geography teachers and 206 students. Data were analysed using descriptive statistics, normality tests, Pearson correlation analysis, and simple linear regression. The results indicate that: (1) the ecopedagogical approach was implemented effectively at a high level (mean scores ranging from 1.88 to 1.95), although the indicators related to the use of the environment as a learning setting (1.90) and as learning materials (1.88) showed the lowest scores; (2) students’ ecological intelligence was also categorized as high (mean scores ranging from 1.59 to 1.98), with relatively lower performance in ecological systems understanding (1.59) and sustainable practice skills (1.86); and (3) correlation analysis revealed a significant positive relationship between ecopedagogical approaches and ecological intelligence (r = 0.430; p < 0.05), with a contribution of 18.5%.